2004
DOI: 10.1677/joe.1.05773
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid down-regulation of rat glucocorticoid receptor does not involve differential promoter regulation

Abstract: The level of expression of the glucocorticoid receptor (GR) is the principal determinant of glucocorticoid sensitivity in most cells. GR levels are permanently 'set' in a tissue-specific manner in response to the perinatal environment, an effect we have previously shown to relate to differential expression of tissue-enriched alternative promoters/exons 1 of the GR gene. In adult animals, GR levels are dynamically regulated around the 'set point' by glucocorticoids themselves, with glucocorticoids downregulatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 39 publications
2
25
0
Order By: Relevance
“…Detailed investigation of the alternative first exon usage in the rat provided no evidence that these exons play a role in this autoregulation (Freeman et al 2004). In these studies expression of exon 1 variants was observed to be concomitantly and uniformly regulated by dexamethasone.…”
Section: Discussionmentioning
confidence: 85%
“…Detailed investigation of the alternative first exon usage in the rat provided no evidence that these exons play a role in this autoregulation (Freeman et al 2004). In these studies expression of exon 1 variants was observed to be concomitantly and uniformly regulated by dexamethasone.…”
Section: Discussionmentioning
confidence: 85%
“…In addition, reduced PVN-CRH levels attenuate ACTH and corticosterone release after subsequent stress Avishai-Eliner et al, 2001), as found in handled rats already at P23 (Avishai-Eliner et al, 2001). Lower corticosterone levels promote expression of hippocampal GR (Reul and de Kloet, 1985;Kalinyak et al, 1987;Freeman et al, 2004) and an efficient shut-off of hormonal stress responses, yielding the phenotype of attenuated HPA axis function typical of adult rats handled early in life (Plotsky and Meaney, 1993;Fenoglio et al, 2005).…”
Section: Fos Induction In Pvt Requires Recurrent Handlingmentioning
confidence: 92%
“…In vivo, adrenalectomy lowers liver and hippocampal 11␤-HSD1 expression in the short-term, but enzyme activity subsequently recovers (317), much like GR itself (202,292). Conversely, elevated glucocorticoids in intact animals increase 11␤-HSD1 in some tissues (adipose tissue, perinatal lung) but not in others (liver) (52, 465,650).…”
Section: F 11␤-hsd1 Regulationmentioning
confidence: 99%